2017
DOI: 10.1177/1474515116687222
|View full text |Cite
|
Sign up to set email alerts
|

Depression in patients with peripheral arterial disease: A systematic review

Abstract: There is a critical need to address depression in peripheral arterial disease patients, particularly those with characteristics that place them at increased risk. Vascular care providers appear to be the primary contact for assessing depressive symptoms, and once identified, integrated mental health providers may intervene to prevent the worsening of both depression and peripheral arterial disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 77 publications
7
37
0
3
Order By: Relevance
“…Additionally, older patients with comorbidities have more depression and anxiety. 17,33 In this context, this study demonstrated that there was an association between these disorders and SAH, as reported in the available literature. 17,[34][35][36] However, it cannot be concluded whether SAH is one of the causes of these disorders in vulnerable patients, whether it is an aggravating factor, whether these disorders predispose patients to developing SAH, or whether there is actually a bidirectional relationship.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Additionally, older patients with comorbidities have more depression and anxiety. 17,33 In this context, this study demonstrated that there was an association between these disorders and SAH, as reported in the available literature. 17,[34][35][36] However, it cannot be concluded whether SAH is one of the causes of these disorders in vulnerable patients, whether it is an aggravating factor, whether these disorders predispose patients to developing SAH, or whether there is actually a bidirectional relationship.…”
Section: Discussionsupporting
confidence: 83%
“…1,9,15,[17][18][19]35,36 Another point that it is indispensable to discuss is that both anxiety and depression are risk factors for CVD, such as AMI, stroke, and PAD. 1,15,17,30,[34][35][36][37][38] This could be because patients with anxiety/depression tend to have a less healthy lifestyle, with dietary errors and without physical exercise, 33,39 as was observed in our sample, the great majority of whom did not do regular physical exercise. However, in contrast to some other studies, 33,36 this factor did not affect the presence of depression.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…10 Despite evidence of an association between depression and cardiovascular health independent of behavioral mechanisms, efforts aimed at understanding the pathophysiological processes linking depression and PAD remain limited. 15,21 One proposed mechanism involves modification of the immune response. PAD is a disease of atherosclerosis, with inflammation driving critical pathologic processes from plaque formation to thrombus rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Original papers calculating the subjective part of life quality are often affected by the psychological state of the atherosclerotic patient, which includes depression, anxiety and stress . (14,15,16) Causes of psycho-emotional disorders . (9,15,19,20) Impact of different treatment options on life quality was also assessed by different studies.…”
mentioning
confidence: 99%